Affect-aware tutors: recognising and responding to student affect. (5th October 2009) - Woolf, Beverly; Burleson, Winslow; Arroyo, Ivon; Dragon, Toby; Cooper, David; Picard, Rosalind
Theories and technologies are needed to understand and integrate the knowledge of student affect (e.g., frustration, motivation and self-confidence) into learning models. Our goals are to redress the cognitive versus affective imbalance in teaching systems, develop tools that model student affect and build tutors that elicit, measure and respond to student affect. This article describes our broad approach towards this goal and our three main objectives: develop tools for affect recognition, interventions in response to student affect, and emotionally animated agents.